Cloud computing in remote sensing - Wang, Lizhe, 1974-; Yan, Jining; Ma, Yan (Computer scientist) (Boca Raton, Florida : CRC Press, 2019)
This book provides the users with quick and easy data acquisition, processing, storage and product generation services. It describes the entire life cycle of remote sensing data and builds an entire high performance remote sensing data processing system framework. It also develops a series of remote sensing data management and processing standards. Features: Covers remote sensing cloud computing Covers remote sensing data integration across distributed data centers Covers cloud storage based remote sensing data share service Covers high performance remote sensing data processing Covers distributed remote sensing products analysis
"Remote sensing and cloud computing" -- Remote sensing data integration in a cloud computing environment -- Remote sensing data organization and management in a cloud computing environment -- High performance remote sensing data processing in a cloud computing environment -- Programming technologies for high performance remote sensing data processing in a cloud computing environment -- "Construction and management of remote sensing production -- Infrastructures across multiple satellite data centers" -- Remote sensing product production in an openstack-based cloud computing environment -- Knowledge discover and information analysis from remote sensing big data -- "Automatic construction of cloud -- Computing infrastructures in -- Remote sensing" -- "Security management in a remote-sensing-oriented cloud computing environment" -- "A cloud-based remote sensing information service system design and implementation".
OCLC-licensed vendor bibliographic record.
Keywords: Remote sensing -- Data processing; Cloud computing; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design; MATHEMATICS / General